Preliminary Evaluation of Nickel Silicide (NiSi12-wt%) Laser Cladding for Enhancing Microhardness and Corrosion Resistance of S355 Steel - Mohammad Ibrahim; Christopher Hulme; Geir Grasmo; Ragnhild E. Aune (Metals)
S355 construction steel, a commonly used mild steel due to its exceptional strength, is prone to environmental degradation, especially pitting corrosion in highly corrosive marine environments. To address this vulnerability, applying a surface layer of nickel silicide (NiSi) cladding on such components could offer a solution, given that NiSi-based alloys are known for their high corrosion resistance and exceptional mechanical properties. Thus, the present study has investigated the corrosion resistance and microhardness of the NiSi12-wt% cladding deposited onto substrates of S355 steel using laser metal deposition. An accelerated ASTM G48 corrosion test and a Vickers microhardness test were conducted in a solution of 6% ferric chloride (FeCl3) solution at room and elevated temperatures to represent marine environments, with uncladded sheet substrates exposed to the same test environments as a reference. All exposed S355 steel samples, with and without cladding, underwent microhardness testing and were characterized using light optical microscopy (LOM) and low-voltage field emission scanning electron microscopy (LVFESEM). The findings indicate that the NiSi12-wt% cladding significantly enhances the corrosion resistance and mechanical properties of the S355 steel samples, showcasing its potential for use in marine and industrial environments where corrosion and mechanical wear are expected.